Predicting Compliance in Voice Therapy using the Voice Handicap Index - Evans, Kristen N. (East Carolina University, 2010)
Research indicates that it is not uncommon for patients to cancel or postpone scheduled appointments for speech therapy designed to improve the voice, i.e., voice therapy. The purpose of this study is to determine if patient perceptions of their voice and vocal problems will predict which patients exhibit noncompliance with a voice therapy program. The present study also analyzed the effects of demographic variables (i.e. age, gender, occupation, etc.) on patient compliance with voice therapy. Â  Twenty-five patient participants were included in this study. Before undergoing voice therapy, these participants were asked to complete the Voice Handicap Index (VHI) in order to obtain a subjective measure of how their vocal "problems" have affected their everyday lives: physically, emotionally, and functionally. The VHI is a standardized patient attitude rating scale that has been shown to document similar issues with patient compliance. Prior to this study, however, variables including occupation, type of insurance coverage, and driving distance from the clinic were not included in those analyses. The individual questions of the VHI were also analyzed in comparison to adherence to therapy recommendations. Descriptive analyses of the data revealed that the VHI scores and responses to individual VHI questions provided no practical significance in predicting patient compliance or noncompliance to voice therapy. In addition, analyses of demographic variables did not offer information that had practical significance regarding patient compliance or noncompliance to therapy.
Keywords: Health Sciences, Speech Pathology; Voice Disorders; Voice Training; Voice Physiology; Voice Disorders--diagnosis; Rehabilitation of Speech and Language Disorders; Voice Disorders--therapy; Voice Quality; Patient Compliance; Psychosocial Factors